PENGUATAN BUDAYA MUTU MELALUI SUPERVISI AKADEMIK DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Kurniyanti, Wiwin; Yustina Neny Hastuti; Wahyu Warastuti; Anam Sutopo; Sabar Narimo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the enhancement of quality culture through the implementation of academic supervision in the Merdeka curriculum at elementary schools. This study employs a qualitative approach with a case study research design. Data collection techniques include interviews, observations, and documentary studies. The research location is at SD Negeri 03 Gumeng, Jenawi, Karanganyar. The findings indicate that academic supervision activities are conducted to assist teachers in implementing the Merdeka curriculum to strengthen the school's quality culture. In terms of planning, the principal involves all teacher elements in planning academic supervision programs. In terms of implementation, the principal directly participates in academic supervision activities in classrooms, selecting approaches, models, and techniques suitable for teacher characteristics. Regarding follow-up, the principal provides appropriate actions based on supervision outcomes.